Air and missile defense systems engineering - Boord, Warren J.; Hoffman, John B., 1957- (Taylor & Francis/CRC Press, 2016)
Air and Missile Defense Systems Engineering fills a need for those seeking insight into the design procedures of the air and missile defense system engineering process. Specifically aimed at policy planners, engineers, researchers, and consultants, it presents a balanced approach to negating a target in both natural and electronic attack environmen.
Keywords: Ballistic missile defenses.; Air defenses.; Systems engineering.; elektronické knihy; electronic books